Association between adherence to the Dietary Approaches to Stop Hypertension diet with food security and weight status in adult women. Issue 5 (10th June 2018) - Tabibian, Saeideh; Daneshzad, Elnaz; Bellissimo, Nick; Brett, Neil R.; Dorosty‐Motlagh, Ahmad R.; Azadbakht, Leila
Abstract : Aim: To investigate the association between adherence to the Dietary Approaches to Stop Hypertension (DASH) diet with food security and weight status in adult women. Methods: This cross‐sectional study was carried out in 227 women—20–50 years of age—who were referred from 10 health centres. Dietary intakes were assessed using validated food frequency questionnaires. The DASH score was calculated using the Fung method based on eight food and nutrient components (high intake of fruits, vegetables, whole grains, nuts and legumes, low‐fat dairy, low intakes of red and processed meats, sweetened beverages and sodium). The United States Department of Agriculture (USDA) household food security questionnaire was used to assess food security status. Results: The prevalence of food insecurity was 33.9%. A greater percentage of overweight and obese people were in the food insecure group ( P  = 0.006). In addition, the prevalence of overweight and obese people was lower with greater adherence to the DASH dietary pattern ( P  = 0.017). After controlling for age and energy intake, participants in the highest tertile of adherence to DASH diet had 66% lower odds of overweight and obesity than those in the lowest tertile (odds ratio (OR): 0.34; 95% confidence interval (CI): 0.15; 0.79). This relationship of DASH diet tertile and overweight and obesity was significant for both food secure women (OR: 0.54, 95% CI: 0.23; 0.97) and food insecure women (OR: 0.35, 95% CI: 0.06; 0.42). Conclusions: Adherence to the DASH diet is associated with a reduced risk of overweight and obesity, based on body mass index, in both food secure and insecure Iranian women.